Nineteenth- and twentieth-century semi-quantitative surface ozone along subtropical European to tropical Africa Atlantic coasts - J. A. Añel; J. A. Añel; J.-C. Antuña-Marrero; J.-C. Antuña-Marrero; A. Cid Samamed; C. Pérez-Souto; L. de la Torre; M. A. Valente; Y. Brugnara; A. Saiz-Lopez; L. Gimeno; L. Gimeno (Earth System Science Data)
Tropospheric ozone (O3) plays a key role in the climate system. Studying pre-industrial tropospheric O3 implies two important challenges: (i) the lack of observational records prior to the late 19th century, which hampers the understanding of long-term climate trends (given the crucial role of O3), and (ii) and the uncertainties in quantitative tropospheric O3 values in a non-polluted atmosphere across the planet. The ozonoscope was the first instrument used to measure ozone. It offered semi-quantitative estimates of surface O3 when no other measurements were available. Despite their potential value, the digitization, curation, and publication of ozonoscope data remain largely unexplored. In this work, we initiate an effort to rescue surface O3 ozonoscope records by compiling them in a new data collection. We include data from 23 observatories covering Portugal and the African Atlantic regions, providing a latitudinal span from the extratropics in the Northern Hemisphere to the tropics in the Southern Hemisphere. This record represents the most extensive ozonoscope data series to date, spanning 50 years of daily data and 58 years of monthly data, from 1855 to 1913. This record represents the most extensive ozonoscope data series to date, spanning 50 years of daily data and 58 years of monthly data, from 1855 to 1913. The data series is available from https://doi.org/10.1594/PANGAEA.969259 (Añel et al., 2024a) and https://doi.org/10.1594/PANGAEA.969241 (Añel et al., 2024b), respectively.